Designing An Interoperable Cloud Computing Framework For Banking Industry (Ethiopia As A Model) - Sisay Tigistu, Tigistu (ASTU, 2017)
Banking industries are a catalyst for a certain countries economy as their role in converting surplus to deficit. Due to the effect of globalization and advancement in technology the business environments are highly dynamic and people needs to access their money in the bank just as in their pocket. To answer this fast access need of a customer it is difficult for a single bank because it needs billions of dollars to afford enough banking access channels and to open a new branch office. The current banking architecture in Ethiopia has many redundancies, limited service deliveries, has no advantages of cost from the bank's point of view even from the customers. To solve the existing problem in banking industry we have proposed to design an interoperable cloud computing framework that serves the banking community and enables to perform inter-banking transaction easily and to minimize the technological costs through interview and literature review on cloud computing as the research methodology. The result obtained from the interview shows that no single bank in Ethiopia can afford enough access channel to serve their rural to urban customers. Additionally, the recent attempt to integrate the banking channel has got a performance challenge due to redundant switching solution. The proposed framework is based on community cloud deployment model because of its suitability for an organization having similar business agenda and security requirements and has cost advantage over the private cloud and security advantage over the public cloud. The framework also uses SaaS (Software as a Service) and IaaS (Infrastructure as a Service) service delivery model in the way that new organizations signed for a SaaS also request their infrastructure requirements like storage, processor, and RAM (Random Access Memory) requirement. The proposed framework has designed by considering security, interoperability and other external systems. When any banking industry signed up to use EBICC (Ethiopian Banking Industry Community Cloud) the system allocate a virtual server which has a core banking system and other management software. Finally, the prototype of the designed framework has been developed using JEE (Java Enterprise Edition) architecture to show the validity of the framework.
Keywords: Cloud computing, Interoperability, Banking Industry